2019
DOI: 10.1001/jamaoncol.2019.0081
|View full text |Cite
|
Sign up to set email alerts
|

Association of Expanded VA Hospice Care With Aggressive Care and Cost for Veterans With Advanced Lung Cancer

Abstract: IMPORTANCE Medicare hospice beneficiaries discontinue disease-modifying treatments because the hospice benefit limits access. While veterans have concurrent access to hospice care and Veterans Affairs (VA) Medical Center (VAMC)-provided treatments, the association of this with changes in treatment and costs of veterans’ end-of-life care is unknown. OBJECTIVE To determine whether increasing availability of hospice care, without restrictions on disease-modifying treatments, is associated with reduced aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Moreover, these points of care, being indicators of greater intensity of care, are made more critical in that they likely affect quality of life during the patient's final month. A recent study showed that increasing hospice care was associated with less aggressive medical treatment and lower costs . Our results provide evidence that racial‐ethnic minority patients enrolled in hospice much less frequently than NH white patients.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, these points of care, being indicators of greater intensity of care, are made more critical in that they likely affect quality of life during the patient's final month. A recent study showed that increasing hospice care was associated with less aggressive medical treatment and lower costs . Our results provide evidence that racial‐ethnic minority patients enrolled in hospice much less frequently than NH white patients.…”
Section: Discussionsupporting
confidence: 54%
“…[64][65][66][67] Of note, racial/ethnic minorities in the U.S. are also generally less likely to use palliative care and hospice services, compounding high end-of-life expenditures as hospital-based end-of-life care is more likely to be aggressive, and therefore costly, in comparison. [68][69][70][71] Our high terminal phase cost estimates for racial/ethnic minorities may reflect these realities. The end-of life period, however, is not the only point at which low…”
Section: Plos Onementioning
confidence: 92%
“…[19][20][21][22][23] Collectively, our findings argue for stronger efforts to meld curative and palliative approaches to care earlier in the illness trajectory for patients with advanced kidney disease and to foster more seamless and patient-and family-centered transitions to hospice. [24][25][26] Our study also offers useful insights about the unintended consequences of restricting access to concurrent dialysis and hospice care. Documentation in the EMRs of members of this cohort provides concrete evidence that being forced to choose between dialysis and hospice can cause undue suffering and discourage, delay, or prevent hospice enrollment.…”
Section: Discussionmentioning
confidence: 91%